2018
DOI: 10.1002/jso.25032
|View full text |Cite
|
Sign up to set email alerts
|

Free vascularized fibula grafting in the operative treatment of malignant bone tumors of the upper extremity: A systematic review of outcomes and complications

Abstract: FVFG in the treatment of malignant bony neoplasms of the upper extremity has a high rate of union and good overall outcomes; however, postoperative complication rates are high. A greater degree of standardization is needed in the reporting of patient-centered outcomes to facilitate future comparative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 95 publications
1
38
1
3
Order By: Relevance
“…Since the very low incidence rate of forearm, Daecke [12] summarized 33 cases of osteosarcoma through multicenter study of Cooperative Osteosarcoma Study Group (COSS), which found 60.6% of the tumors in distal radius and only one tumor in proximal ulna. The common tumors of forearm bone are osteosarcoma, Ewing's sarcoma, undifferentiated pleomorphic sarcoma and chondrosarcoma, which are consistent with that osteosarcoma was the most common tumor in upper limb reported by Landau [13]. But Ewing's sarcoma and chondrosarcoma were usually sporadic and individual cases [8,[14][15][16].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Since the very low incidence rate of forearm, Daecke [12] summarized 33 cases of osteosarcoma through multicenter study of Cooperative Osteosarcoma Study Group (COSS), which found 60.6% of the tumors in distal radius and only one tumor in proximal ulna. The common tumors of forearm bone are osteosarcoma, Ewing's sarcoma, undifferentiated pleomorphic sarcoma and chondrosarcoma, which are consistent with that osteosarcoma was the most common tumor in upper limb reported by Landau [13]. But Ewing's sarcoma and chondrosarcoma were usually sporadic and individual cases [8,[14][15][16].…”
Section: Discussionsupporting
confidence: 68%
“…Tumors located in ulna and proximal forearm showed signi cantly higher risk of local recurrence in univariate analysis, which was not found in previous studies [7,12,13]. It is considered that soft tissue sarcoma of forearm has been reported in majority before, so tumor size was more concerned and was associated with recurrence [19].…”
Section: Discussionmentioning
confidence: 69%
“…Complication rates of vascularized fibula grafts have been reported to be 7%-35% and 3.3%-23.1% in several cases (23,25). Although no serious complication was seen in our patients, two of them were treated early due to superficial infection.…”
Section: Discussionmentioning
confidence: 47%
“…Graft nonunion was most common (24.1%), occurring in four malignant bone tumors, two cases of pseudoarthrosis, and one case of osteomyelitis. Although the literature on the effect of chemotherapy on nonunion in FVFG is mixed, 22,31,[38][39][40][41][42] in our own series, more than half of the cases of nonunion occurred in patients receiving chemotherapy. In remaining the malignant bone tumor patients, chemotherapy also appeared to lead to slower rates of bony union (average of 7.5 months).…”
Section: Discussionmentioning
confidence: 51%